Electronic Data Interchange In The Automotive Industry In Morocco : Toward The Optimization Of Logistics Information Flows - Bahija, Jardini; Malika, Elkyal; Mostapha, Amri (European Scientific Journal, ESJ, 2016)
The information systems conducted by the requirements of the internationalization of activities, by the organization of firms in networks and by the evolution of Information and Communication Technology, tend more and more toward the sharing of information in real time. The Electronic Data Interchange (EDI) is among the tools that guarantee this exchange. EDI is a quick and effective means of transfer of business documents and ensures the optimization of the information flows of and their synchronization with the physical flows in the Supply chain. The objective of this study is to answer this research question “how the automobile industry in Morocco uses the EDI technology to optimize its flows?” We chose to adopt a case study approach to observing the reality of the practice of the EDI and its use as a tool for optimizing information flows. Thus, this article is the result of literature review and of the content analysis of semi-structured interviews conducted with professionals in the automotive industry.